The role of the ATM/Chk/P53 pathway in mediating DNA damage in hand-foot syndrome induced by PLD. (4th January 2017) - Yang, Jie; Qiao, Long; Zeng, Zhen; Wang, Junnai; Zhu, Tao; Wei, Juncheng; Wu, Mingfu; Ye, Shuangmei; Huang, Xiaoyuan; Ma, Ding; Liu, Ronghua; Gao, Qinglei
Highlights: PLD affects the proliferation inhibition and apoptosis in HaCaT cells in vitro . PLD enhances zebrafish skin pigmentation and induces DNA damage in vivo . PLD damages the HaCaT cells through the ATM/Chk/P53 pathway. The mechanism explains the HFS induced by PLD. Abstract: Pegylated liposomal doxorubicin (PLD) has been approved to treat patients with various types of cancers because it rarely caused side effects, such as cardiotoxicity, in comparison to doxorubicin, but it frequently results in hand-foot syndrome (HFS). This may affect the quality of life and require a reduction in the PLD dose. The pathophysiology of HFS was not well understood. This study was aimed at exploring the mechanism of HFS induced by PLD. We compared the effects of different doses of PLD on the proliferation inhibition and apoptosis in vitro in HaCaT cells and analyzed the skin changes and skin cell DNA damage in vivo using a zebrafish model. The results suggested that very low doses of PLD show a proliferation inhibition (cell cycle arrest at G2/M phase) and an apoptosis phenotype characterized by the ATM/Chk/P53 pathway that mediates DNA damage in vitro in HaCaT cells. In addition, PLD enhanced zebrafish skin pigmentation from the head to the trunk and induced DNA damage (phospho-H2AX staining) and cell death in the skin of zebrafish. The results of the present study suggested potential applications to provide a better understanding of the apoptosis of PLD-treated skin cells and described a simple methodology for detecting a PLD-induced DNA damage response in zebrafish, which may be helpful in preventing and treating HFS.